1989
DOI: 10.1111/j.2044-8309.1989.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup identification and intergroup differentiation: A multicomponent approach

Abstract: The factor structure of an intragroup identification scale was examined. Subjects participating in small groups worked on a decision-making task, complctcd the identification measure and made in-group and out-group evaluations. Three factors reflecting emotional, cognitive and individual/group interdependence aspects of identification accounted for 70,5 percent of the scale's rota1 variance. Based upon these rcsulrs, the identification scale was decomposed into three subscales. Correlations between subscale sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
211
2
19

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(247 citation statements)
references
References 7 publications
9
211
2
19
Order By: Relevance
“…Karasawa (1991) distinguished between identification with the group and identification with group members. Hinkle et al (1989) found evidence for three components: an affect aspect, a cognitive aspect and a group dynamics aspect. Ellemers et al (1999) reported findings indicating three factors of social identification; group self esteem, self categorization and commitment to the group.…”
Section: Three-dimensional Strength Of Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Karasawa (1991) distinguished between identification with the group and identification with group members. Hinkle et al (1989) found evidence for three components: an affect aspect, a cognitive aspect and a group dynamics aspect. Ellemers et al (1999) reported findings indicating three factors of social identification; group self esteem, self categorization and commitment to the group.…”
Section: Three-dimensional Strength Of Identificationmentioning
confidence: 99%
“…Deaux (1996) in a review of the social identification literature argues that cognitive processes, emotional associations and interdependence between group members are all important aspects of the social identification process (see Deaux, 1996, for more detail). Several authors have found empirical evidence for the multidimensional nature of social identification (Cameron & Lalonde, 2001;Ellemers, Kortekaas, & Ouwerkerk, 1999;Hinkle, Taylor, Fox-Cardamone, & Crook, 1989;Jackson, 2002;Jackson & Smith, 1999). Karasawa (1991) distinguished between identification with the group and identification with group members.…”
Section: Three-dimensional Strength Of Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Como existe suporte teórico (Deaux, 1996;Tajfel, 1978) e empírico Hinkle et al, 1989) convincentes para a existência de múltiplas dimensões da identidade social, Cameron (2004) observou que parece incerta a extensão em que as variações das estruturas fatoriais entre os estudos são atribuíveis à variação metodológica. Além disso, conforme observou Cameron (2004), nenhum modelo multidimensional da identidade social tinha sido, ainda, sujeito à análise fatorial confirmatória, dentro e entre diferentes grupos sociais, ou sistematicamente validados vis-à-vis a medidas comparáveis de identificação.…”
Section: Modelo Trifatorial Da Identidade Social E Escala De Identifiunclassified
“…Os itens da Escala de Identificação Social foram constituídos com base: em estudos de Cameron e Lalonde (2001), que desenvolveram uma escala de 28 itens de identificação social, derivados de diferenças de gênero; nos itens de medidas de identidades sociais (Brown et al, 1986;Hinkle et al, 1989) e autoestima coletiva (Luhtanen & Crocker, 1992), bem como, em trabalho anterior sobre a identidade social de mulheres (Gurin & Markus, 1989;Gurin & Townsend, 1986).…”
Section: Modelo Trifatorial Da Identidade Social E Escala De Identifiunclassified